2023
DOI: 10.1177/21676968231194380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Loneliness in Emerging Adulthood: A Qualitative Study

Emma M. Kirwan,
Páraic S. O’Súilleabháin,
Annette Burns
et al.

Abstract: Loneliness, the distressing feeling that accompanies the perception of a person’s social relationships as inadequate, is common in emerging adulthood. This qualitative study explored the experiences and views of loneliness, and the causes of loneliness from the perspective of emerging adults. A youth Research Advisory Group was consulted during the design of the study. Semi-structured interviews were conducted with 27 emerging adults (18–25 years old, M = 20.81, SD = 1.78). Using framework analysis, two key th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, transition from secondary to postsecondary education, leaving home and settling to a new country (particularly for international students) may lead to rupture in existing networks and often require forming new relationships within a short time. Given that transitions are often considered vulnerable periods due to a potential disruption to young adults' existing social network (Kirwan et al, 2023), this study finding indicate that recovery colleges may, support, and promote a sense of connection, and belongingness among young adultsan important component of personal recovery among young adults (Arbour et al, 2023). Building meaningful social connections might have helped young adults to navigate new systems and learning environments and get settled.…”
Section: Discussionmentioning
confidence: 80%
“…For example, transition from secondary to postsecondary education, leaving home and settling to a new country (particularly for international students) may lead to rupture in existing networks and often require forming new relationships within a short time. Given that transitions are often considered vulnerable periods due to a potential disruption to young adults' existing social network (Kirwan et al, 2023), this study finding indicate that recovery colleges may, support, and promote a sense of connection, and belongingness among young adultsan important component of personal recovery among young adults (Arbour et al, 2023). Building meaningful social connections might have helped young adults to navigate new systems and learning environments and get settled.…”
Section: Discussionmentioning
confidence: 80%
“…It would also be relevant to consider how other individual factors (e.g., socio-economic status, sexual orientation, and ethnicity) intersect and influence experiences of solitude and indices of maladjustment (see [60] for a similar approach). Also, since this study adopted a quantitative approach with an online questionnaire, using qualitative methods (e.g., interviews and focus groups) could provide a deeper understanding of emerging adults' motivations and experiences of solitude [6,61].…”
Section: Limitations Strengths and Future Directionsmentioning
confidence: 99%
“…A study conducted in UK reported that in 595 individuals aged 65 and above, age-related vulnerabilities encompassing physical and psychological factors, such as clinical frailty and geriatric pain, contributed to the manifestation of PG in late-life, with depression and anxiety serving as mediators [ 25 ]. In addition, it was found that loneliness and sense of mastery as age-related factors [ 26 , 27 ] were associated indirectly with excessive gambling via psychological distress in four different country samples of teenagers and emerging adults [ 28 ], thus highlighting the complex effects of age and mental health on gambling.…”
Section: Introductionmentioning
confidence: 99%